KESALAHAN PENGUNAAN KATA SIFAT PADA PIDATO SINGKAT MAHASISWA ANGKATAN 2020 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research discusses about the results of the error analysis using adjectives on student short speeches. The purpose of this study was to describe the errors made by students in use adjectives in recordings of short speeches. This research is aqualitative research with descriptive method. This research was conducted at the Japanese Language Education departement Teacher Training and Education Faculty of the Riau University. The research data was obtained from two themes with total of 56 speeches. The research steps consist of data colletion, data reduction, data presentation and conclusions. The results of this study found 3 types of errors based on linguistic categories. Most frequent errors phonological errors with total 15 errors from 23 erros, morphological errors totaling 6 errors, and syntax errors totaling 2 errors.Key Words: Error Analysis, I-Keyoushi And Na-Keyoushi Adjectives, Japanese Short Speech Recording